SOSIALIASI BALAP LIAR SEBAGAI UPAYA PENGENDALIAN SOSIAL DI SMAN 15 PEKANBARU - Rinaldi, Kasmanto; Maharani, Afrilia Putri; Kumala, Aida Yumi; Yulia, Dinda; Situmorang, Eka Irma; Gustaf, Ghifari Ahmad; Oktaviana, Helma; Taufiqurahman, Ilham; Aufa, Mimi Dwi; Fikri, Muhammad; Zulhairi, Muhammad Al Fayyed (Komunitas Manajemen Kompetitif, 2024)
Teenagers are a national treasure who have a very crucial position in the country's development. To improve the quality of teenagers and to prevent juvenile delinquency, especially in schools, the government issued Presidential Decree 87 No 2017 regarding strengthening character education. Juvenile Delinquency is a type of deviant behavior committed by teenagers. Juvenile delinquency includes all forms of behavior that violate norms carried out by teenagers. The causal factors vary widely, both internally and externally, which require attention. Therefore, to overcome this, guidance from parents is needed along with a positive school environment. This will determine his future. The problems that occur at SMAN 15 Pekanbaru are fighting, and skipping school which usually occur due to the lack of education regarding juvenile delinquency. This socialization was held to educate students at SMAN 15 Pekanbaru. This socialization method was carried out using qualitative methods and resource interviews. The results obtained from this activity are that the violations that often occur at SMAN 15 are illegal racing and fighting. Students also understand the impact of this mischief and participate in socialization well.